Mortgage credits and live assurance - Koláček, Martin; Ducháčková, Eva, 1958-; Daňhel, Jaroslav, 1943-2025; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2009)
Thesis provides an overview of different types of mortgages and mortgage protection assurances available in czech credit and insurance markets. Thesis is composed of detailed description of particular products and case study describing comparison of three types of mortgages: classic anuity mortgage, mortgage with postpone payment of principal in combination with unit linked life assurance, mortgage with postpone payment of principal in combination with investment to securities. The aim was the comparison on the basis of chosen evaluations of unit linked life assurance and securities and determination of boundary percentage value of evaluation by which the combine product become preferable to classic mortgage.
Vedoucí práce: Eva Ducháčková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2010
Rok obhajoby 2010
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses